2001
DOI: 10.1034/j.1398-9995.2001.00100.x
|View full text |Cite
|
Sign up to set email alerts
|

Local side‐effects of inhaled corticosteroids in asthmatic children: influence of drug, dose, age, and device

Abstract: Local side-effects of ICS are common in asthmatic children of all ages, and the device used constitutes the most influential factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
111
1
16

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(134 citation statements)
references
References 27 publications
6
111
1
16
Order By: Relevance
“…Os efeitos locais incluem tosse durante a inalação, secura na garganta, rouquidão, disfonia e candidíase oral 54,55 . A higienização oral após o uso do CEI auxilia na redução desses efeitos dose-dependentes.…”
Section: Efeitos Adversos Locaisunclassified
See 1 more Smart Citation
“…Os efeitos locais incluem tosse durante a inalação, secura na garganta, rouquidão, disfonia e candidíase oral 54,55 . A higienização oral após o uso do CEI auxilia na redução desses efeitos dose-dependentes.…”
Section: Efeitos Adversos Locaisunclassified
“…Por não ser ativada na mucosa oral, a CIC proporciona uma chance significativamente menor de efeitos adversos locais. O uso de dispositivos pode promover menor deposição na orofaringe 54,55 .…”
Section: Efeitos Adversos Locaisunclassified
“…We believe a dual effect underlies these findings: (1) the improved strength may be related to some degree of transient muscle fiber hypertrophy. Tongue hypertrophy has been reported in children treated with ICS, 43,44 as soon as 4-7 weeks into treatment. 44 This effect is believed to be partly due to muscle fiber hypertrophy 43,44 ; (2) the reduced endurance could reflect incipient functional deficits, building-up as a result of differential effects on the tissue compartments comprising the tongue, such as (a) unmasked preexistent inflammation-induced remodeling/dysfunction, and/or (b) a direct drug effect on the muscle fibers.…”
Section: Changes In the Tongue Function In Response To Fp Therapy Andmentioning
confidence: 99%
“…Various studies have been conducted assessing the association between ICS and the occurrence of oral candidiasis [9][10][11][12]. One review reported incidence rates between 0 and 70 %, based on four studies performed between 1974 and 1990 using different diagnostic criteria [2].…”
Section: Introductionmentioning
confidence: 99%